Manufacture of banana powder - Deang, Amado; Quirim, Julius; Simbulan, Rosalie (Diliman, Quezon City College of Engineering, 1989)
The plant location we thought suitable for our purpose is Davao City. Here, supply of bananas is speedy and plentiful. There is also a dependable supply of water, and adequate power supply. Sewage disposal facilities are available, and so is transportation. Even manpower is not a problem; it is even on the cheap side. This plant designed to manufacture banana powder from ripe Cavendish bananas through the use of spray drier has a capacity of 517 kg/day, with a profit of P14 kg and an annual manufacturing cost of P5,197,800. It has a fixed capital investment of P15,272,490. The breakeven point is at 81,760 kg per year and pay-out time is in 4 years.
Plant Design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Agricultural processing plants; Banana products